2001
DOI: 10.1021/la010975c
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Probe and Pulsed Field Gradient NMR Study of Aqueous Solutions of Poly(ethylene oxide)−Poly(propylene oxide)−Poly(ethylene oxide) Block Copolymer F88

Abstract: In aqueous solutions of the triblock copolymer F88 (EO96PO39EO96) micelle formation has been studied by means of dual fluorescence of the probe molecule 1,3-bis(1-pyrene)propane monitoring viscosity changes in its microenvironment. Mobility changes of the polymer molecules on micellization were followed by means of pulsed field gradient (PFG) NMR. These results complement a recent detailed study of cis−trans isomerization of azo dyes as “kinetic probes” for structure formation in aqueous solutions of F88 (Lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…We discussed the temperature of the maximum of D determined by means of PFG NMR measurements as cmT of "probe-free" samples [15,16]. Moreover, we have found that ln(bulk viscosity) vs. 1/T plots of 10% F88 solutions, and density vs. 1/T plots of solutions of ≥5% P85 and 10% F88, respectively, show also inflection points that can be assigned to micelle formation (see Figs.…”
Section: Cmt-datamentioning
confidence: 94%
See 4 more Smart Citations
“…We discussed the temperature of the maximum of D determined by means of PFG NMR measurements as cmT of "probe-free" samples [15,16]. Moreover, we have found that ln(bulk viscosity) vs. 1/T plots of 10% F88 solutions, and density vs. 1/T plots of solutions of ≥5% P85 and 10% F88, respectively, show also inflection points that can be assigned to micelle formation (see Figs.…”
Section: Cmt-datamentioning
confidence: 94%
“…c Contrary to P85, self-diffusion coefficients of 10% F88 molecules determined by PFG NMR measurements [15] monitor a significant temperature difference between the cmT in H 2 O and D 2 O. It suggests that the stronger deuterium bonding compared to hydrogen bonding between D 2 O molecules and of D 2 O with the longer ethylene oxide chains of F88 contributes more effectively to the reduction of the mobility of the copolymer molecules in the case of F88 compared to P85, which have equal PPO chain length.…”
Section: Solutions Of P85mentioning
confidence: 99%
See 3 more Smart Citations